2014
DOI: 10.1038/npp.2014.94
|View full text |Cite
|
Sign up to set email alerts
|

Adenosinergic Regulation of Striatal Clock Gene Expression and Ethanol Intake During Constant Light

Abstract: Circadian rhythm and sleep disruptions occur frequently in individuals with alcohol use disorders (AUD) and present significant barriers to treatment. Recently, a variant of adenosine transporter, equilibrative nucleoside transporter 1 (ENT1), was associated with the cooccurrence of sleep problems and AUD. We have previously shown that mice lacking ENT1 (ENT1 KO) have reduced adenosine levels in the striatum and drink more alcohol compared with wild types (WT). However, it is unknown whether ENT1 deletion disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
(99 reference statements)
1
15
0
Order By: Relevance
“…Interestingly, levels of extracellular adenosine peak early during circadian nighttime and progressively increase throughout the course of the circadian day (Porkka-Heiskanen et al, 1997 ). This circadian rhythm is synchronized with the cyclic expression of transporters responsible for regulating synaptic adenosine, including ENT1 (Ruby et al, 2014b ). Interestingly, disruption of ENT1 function via genetic knockout reduces synaptic adenosine concentrations and lowers the peak expression of clock genes, including Per2 (Ruby et al, 2014b ).…”
Section: Purinergic Signaling and Circadian Rhythmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, levels of extracellular adenosine peak early during circadian nighttime and progressively increase throughout the course of the circadian day (Porkka-Heiskanen et al, 1997 ). This circadian rhythm is synchronized with the cyclic expression of transporters responsible for regulating synaptic adenosine, including ENT1 (Ruby et al, 2014b ). Interestingly, disruption of ENT1 function via genetic knockout reduces synaptic adenosine concentrations and lowers the peak expression of clock genes, including Per2 (Ruby et al, 2014b ).…”
Section: Purinergic Signaling and Circadian Rhythmsmentioning
confidence: 99%
“…This circadian rhythm is synchronized with the cyclic expression of transporters responsible for regulating synaptic adenosine, including ENT1 (Ruby et al, 2014b ). Interestingly, disruption of ENT1 function via genetic knockout reduces synaptic adenosine concentrations and lowers the peak expression of clock genes, including Per2 (Ruby et al, 2014b ). Furthermore, ENT1 KO mice display altered circadian rhythms marked by early onset of an elongated and hyperactive active phase (Ruby et al, 2014b ).…”
Section: Purinergic Signaling and Circadian Rhythmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, there is first evidence that adenosine might exert an influence on the circadian clockwork. It has been shown that A 2A receptor antagonism and knock-out of an equilibrative adenosine transporter (equilibrative nucleoside transporter 1 [ENT1]) is linked to blunted Per2 expression in the striatum, but not in the SCN [ 99 ]. Yet, to our knowledge, a direct link between the sleep-homeostatic regulation of adenosine ( i.e.…”
Section: Sleep-wake Regulation: Concepts and Empirical Evidencementioning
confidence: 99%
“…Chen et al, 2010; Choi et al, 2004; M. R. Lee et al, 2013; Nam, Hinton, et al, 2013; Nam et al, 2011; Ruby et al, 2014; Ruby, Walker, An, Kim, & Choi, 2011). Thus, studies from multiple labs support a role for adenosine in controlling alcohol-seeking behavior.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%